HIF Prolyl Hydroxylase Inhibitors for COVID-19 Treatment: Pros and Cons - Poloznikov, Andrey A.; Nersisyan, Stepan A.; Hushpulian, Dmitry M.; Kazakov, Eliot H.; Tonevitsky, Alexander G.; Kazakov, Sergey V.; Vechorko, Valery I.; Nikulin, Sergey V.; Makarova, Julia A.; Gazaryan, Irina G. (Frontiers in Pharmacology, 2021)
The review analyzes the potential advantages and problems associated with using HIF prolyl hydroxylase inhibitors as a treatment for COVID-19. HIF prolyl hydroxylase inhibitors are known to boost endogenous erythropoietin (Epo) and activate erythropoiesis by stabilizing and activating the hypoxia inducible factor (HIF). Recombinant Epo treatment has anti-inflammatory and healing properties, and thus, very likely, will be beneficial for moderate to severe cases of COVID-19. However, HIF PHD inhibition may have a significantly broader effect, in addition to stimulating the endogenous Epo production. The analysis of HIF target genes reveals that some HIF-targets, such as furin, could play a negative role with respect to viral entry. On the other hand, HIF prolyl hydroxylase inhibitors counteract ferroptosis, the process recently implicated in vessel damage during the later stages of COVID-19. Therefore, HIF prolyl hydroxylase inhibitors may serve as a promising treatment of COVID-19 complications, but they are unlikely to aid in the prevention of the initial stages of infection.